2010
DOI: 10.1016/j.ecolecon.2009.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Valuing ecosystem services from wetlands restoration in the Mississippi Alluvial Valley

Abstract: This study assesses the value of restoring forested wetlands via the U.S. government's Wetlands Reserve Program (WRP) in the Mississippi Alluvial Valley by quantifying and monetizing ecosystem services. The three focal services are greenhouse gas (GHG) mitigation, nitrogen mitigation, and waterfowl recreation. Site-and region-level measurements of these ecosystem services are combined with process models to quantify their production on agricultural land, which serves as the baseline, and on restored wetlands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(129 citation statements)
references
References 40 publications
1
120
0
5
Order By: Relevance
“…Literature on the valuation of ecosystem services has increased considerably in recent years (Chen et al, 2009;Jenkins et al, 2010;Tallis and Polasky, 2009;Tong et al, 2007). However, little work has been done to quantify these services, which poses a major challenge to their research application to actual land management and economic and policy decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the valuation of ecosystem services has increased considerably in recent years (Chen et al, 2009;Jenkins et al, 2010;Tallis and Polasky, 2009;Tong et al, 2007). However, little work has been done to quantify these services, which poses a major challenge to their research application to actual land management and economic and policy decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In Lake Victoria, Simonit and Perrings (2011) calculated the value of regulating services-nutrient buffering functions of wetland to improve the ecosystem service compensation scheme, indicated that the total cost of the payments for nutrient buffering services is 3.86 M dollars per year. Jenkins et al (2010) emphasized the significance of the regulating services of wetland in the Mississippi Alluvial Valley for advising the government to take conservation practices on wetland ecosystem services (Faulkner et al, 2011). Thirdly, cultural services involved not only the visual enjoyment provided by the hydrological landscape, but also elevating the utility of human.…”
Section: Positive Effect Of the Changes Of Regional Hydrological Ecosmentioning
confidence: 99%
“…Provides unique and aesthetic landscape, suitable habitat for diverse fauna and flora Tourism, recreation, education, and research Creel and Loomis (1992), Bergstrom and Stoll (1993), Cooper and Loomis (1993), King and Lester (1995), Bateman and Langford (1997), Hammitt et al (2001), Johnston et al (2002), Carlsson et al (2003), Othman et al (2004), Brouwer and Bateman (2005), Birol et al (2006), Birol and Cox (2007), Do and Bennet (2008), Jenkins et al (2010).…”
Section: Maintenance Of Temperature Precipitationmentioning
confidence: 99%
“…Water purification Breaux et al (1995), Gren (1995), Byström (2000), Yang et al (2008), Jenkins et al (2010) Generates biogeochemical activity, sedimentation, biological productivity Carbon sequestration Jenkins et al (2010) Climate regulation and stabilization…”
Section: Valuing Wetland Ecosystem Servicesmentioning
confidence: 99%
See 1 more Smart Citation